Gestión Administrativa Y Su Incidencia En Las Funciones De Las Áreas Operativas De La Federación Deportiva De Los Ríos - Mazacón Gómez, Martha Narcisa (2014)
The Sports Federation of Los Ríos subject to the research study is dedicated to the training of athletes of elite, seeking the supply of the service provided to the satisfaction of each of the athletes from various sports and community in general, that's why each of the administrative department of the Sports Federation of Los Ríos has macro processes to meet performance requirements and documents, respecting the enabling responsible for each activity to take better control of the operations performed by each employee. This work contains the motives and reasons which led to make this thesis, the problem situation, the problem statement, objectives and assumptions used in the development of the thesis. The theoretical framework that will serve as a basis for develop relevant issues, according to the definitions found in both textbooks and websites, detailed context national and institutional of the National Federation of Ecuador and The Sports Federation Provincial of Los Ríos, respectively. It presents and analyzes the results obtained from the surveys and interviews with employees and managers of the institution, establishing conclusions and facilitates recommendations to define a proposal to improve the processes and response time requirements, all documents are attached and information used, which were the tools to gather essential information that helped to develop this research.